Extensive fluid–rock interaction and pressure solution in a UHP fluid pathway recorded by garnetite, Lago di Cignana, Western Alps. (11th January 2021) - van Schrojenstein Lantman, Hugo W.; Scambelluri, Marco; Gilio, Mattia; Wallis, David; Alvaro, Matteo
Abstract: This study combines the microstructural and petrological analysis of garnet and its inclusions in quartzite‐hosted garnetite from the ultrahigh‐pressure Lago di Cignana metaophiolite (Western Alps). We present a comprehensive record of metamorphism, compaction, and the state of stress during interaction between oceanic metasediments and infiltrating fluids along a major open‐system fluid pathway. The arrangement of garnet into garnetite layers is attributed to concomitant compaction and dissolution that resulted in the formation of a garnet stylolite. The fluid pulses that were accommodated by this pathway subsequently resulted in several stages of garnet deformation, dissolution, local reprecipitation, and recrystallization. Abundant evidence for pressure solution in garnet, alongside near‐hydrostatic to hydrostatic conditions indicated by elastic strains of quartz inclusions in garnet obtained through Raman spectroscopy, support low differential stresses during fluid–rock interaction. The high degree of dissolution recorded by the garnetite showcases the strong potential for compaction by fluid‐assisted volume loss and mass transfer. Dehydration of subducting rocks with subsequent migration of resulting fluids through the slab provides a mechanism of mass transfer and has the potential to drive compaction and exert control on differential stress along fluid pathways.